PENGARUH TEKNIK PERMAINAN MENYUSUN KATA PADA MATA PELAJARAN BAHASA INDONESIA TERHADAP KEMAMPUAN MEMBACA SISWA KELAS I SDN 24 GELUMBANG - Rini Andika; Djunaidi; Hetilaniar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The background of one of the subjects that must be given in elementary schools is Indonesian.The scope of learning Indonesian in elementary schools includes 4 (four) components of language skills, namely listening / listening, reading, writing, and speaking. The above problem makes the author feel the need to conduct a study entitled "The Effect of Word Arranging Game Techniques on Indonesian Subjects on the Reading Ability of Grade I Students of SDN 24 Gelumbang"This research is to determine whether or not there is an influence of word composing game techniques on the reading ability of grade I students of SDN 24 Gelumbang. Experimental research methods are research methods used to look for the effect of certain treatments (treatments) under controlled conditions. The subjects of this study were grade I students of SD Negeri 24 Gelumbang totaling 24 students. The data collection method uses observation, tests, and documentation. The test instrument is in the form of multiple-choice questions totaling 20 questions to measure the results of students' reading skills. Data analysis technique using Independent Sample T-test. The results showed that the influence of word composing game techniques can improve the learning outcomes of elementary school students in Indonesian subjects which can be seen from the learning results of the hypothesis test (Independent Sample T-Test) in the form of the significance value of this study, which is 0.000< 0.05 which Ho rejected Ha accepted. So it can be concluded that "There is an influence of word composing games in Indonesian subjects on the reading ability of grade I students of SDN 24 Gelumbang".